Dramatic Monologue in Bidart’s Work “Half-Light” (2017) - Wazzan, Suzanne A. (Al-Adab Journal, 2023)
This paper aims at investigating dramatic monologue in Frank Bidart’s poems. It discusses the way Bidart was affected by certain poets in terms of the implication of the dramatic monologue device and the power that affected his implementation and his application of this particular genre. Bidart proposes that a poet has a lot of inner consciousness. He receives various voices so he can visualize how to begin from varied places and keep a certain distance from the voice that expresses out of its sense, agony, or annoyance. Bidart has to examine the reasons for definite feelings at a particular point in time because one’s emotional state should not be considered for granted. However, a poet should keep some distance from the characters in the poem as well as keep a sort of skepticism concerning oneself. This study suggests that Bidart’s dramatic monologue is a contemporary genre that is significantly established at the last stage of his script with the release of his poetic work “Half Light”. The study analysed two poems of Bidart’s work including Old and Young, and Thirst. Results of the study showed that Bidart’s poetic forms and themes relate to many issues including the point of time in which the poet published his poems, the setting and situations, and the poet’s psychological state of mind.